Morfologi Tanaman Bawang Merah (Allium ascalonicum) terhadap Pemberian Mikoriza dan Media Tanam Limbah Kelapa Sawit - Dedi Kurniawan; Siti Khairani (Universitas Sebelas Maret, 2023)
Improvement in onion cultivation techniques need to be done by giving mycorrhizal and palm oil waste as a mixture of growing media for growth and production of onion. This objective of this experiment was to determine the effect of mycorrhizal, growing media, interaction of giving mycorrhizal and production of onion. The design environment used in this study were Randomized Block Design with factorial pattern. The first factor was the inoculation of mycorrhizal consisting of three levels: without inoculation of mycorrhizal, mycorrhizal inoculant 50 and 100 gram/plant. The second factor was the growing media with four levels of growing media: Top soil, Top soil + TKKS (1:1), Top soil + fiber (1:1), and Top soil + sludge (1:1). The results showed that the growing media had a significant effect on leaves total of onion. The growing media of Top soil + sludge was the best treatment for growth and production of onion. The giving mycorrhizal, interaction of giving mycorrhizal and growing media hadn’t a significant effect on plant height and tillers total of onion.